β1- and β3- voltage-gated sodium channel subunits modulate cell surface expression and glycosylation of Nav1.7 in HEK293 cells - Laedermann, Cedric J.; Syam, Ninda; Decosterd, Isabelle; Abriel, Hugues (Frontiers in Cellular Neuroscience, 2013)
Voltage-gated sodium channels (Navs) are glycoproteins composed of a pore-forming α-subunit and associated β-subunits that regulate Nav α-subunit plasma membrane density and biophysical properties. Glycosylation of the Nav α-subunit also directly affects Navs gating. β-subunits and glycosylation thus comodulate Nav α-subunit gating. We hypothesized that β-subunits could directly influence α-subunit glycosylation. Whole-cell patch clamp of HEK293 cells revealed that both β1- and β3-subunits coexpression shifted V1/2 of steady-state activation and inactivation and increased Nav1.7-mediated INa density. Biotinylation of cell surface proteins, combined with the use of deglycosydases, confirmed that Nav1.7 α-subunits exist in multiple glycosylated states. The α-subunit intracellular fraction was found in a core-glycosylated state, migrating at approximately 250 kDa. At the plasma membrane, in addition to the core-glycosylated form, a fully glycosylated form of Nav1.7 ( 280 kDa) was observed. This higher band shifted to an intermediate band ( 260 kDa) when β1-subunits were coexpressed, suggesting that the β1-subunit promotes an alternative glycosylated form of Nav1.7. Furthermore, the β1-subunit increased the expression of this alternative glycosylated form and the β3-subunit increased the expression of the core-glycosylated form of Nav1.7. This study describes a novel role for β1- and β3-subunits in the modulation of Nav1.7 α-subunit glycosylation and cell surface expression.